INFLUENCE OF CALCULATION TEMPERATURE TO HIDROTALSIT Mg / Al WHICH IS DISINTESTED THROUGH UNSECUAL METHOD OF PRESIPITATION - Hasan Adidarma; Sri Handayani; Cahyorini Kusumawardani; Kun Sri Budiasih (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2014)
This research aims to determine the effect of calcination temperature variation from 200°C to 500°C on the Mg/Al hydrotalcite structure. Mg/Al hydrotalcite has been synthesized via a low supersarturated precipitation method with hydrothermal treatment, using Mg(NO3 )2 .6H2 O and Al(NO3 )3 .9H2 O as the raw materials, and base solution of NaOH and Na2 CO3 as the precipitators. Mg/Al hydrotalcite compound synthesized before and after calcination were characterized using fourier transform infrared (FTIR) and X-ray diffractometer (XRD). The results of FTIR and XRD data analysis showed that the calcination of hydrotalcite of Mg/Al at 200o C did not changed the structure of hydrotalcite compounds, calcination at temperatures 300-400o C showed that structure of hydrotalcite compound starts to change form a mixture of magnesium oxide and aluminum, and calcination at 500°C showed that the crystal structure of Mg/Al hydrotalcite has broken to form a mixture of metal oxides, namely MgO (phericlase) with a little mixture of aluminum oxide in the form of θ-Al2O3 and γ-Al2O3.